PENGARUH MEDIA BOOKLET TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU PASIEN DIABETES MELLITUS DALAM PENCEGAHAN KELAINAN PERIODONTAL DI PUSKESMAS II DENPASAR UTARA TAHUN 2018 - Anak Agung Gede Agung; I Nyoman Wirata; Ni Wayan Arini (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Periodontal disorders is one of the risks that can occur at patients with Diabetes Mellitus. The ignorance of patients for prevention and checking their teeth and mouth that caused periodontitis and result in early tooth lossed. The one solution that can be done for Diabetes Mellitus patients in preventing of periodontal disorders is to right brush their teeth regularly. The aim of the study was to analyze the influence of booklet to increase of knowledge, attitude, and behaviour of Diabetes Mellitus patients in prevention of periodontal diseases in prevention of periodontal diseases at Puskesmas II Denpasar Utara in 2018. The type of this study is action research that was in dental health education form to improve the knowledge and behaviour to maintain the healthy teeth to total population that amount to 100 patients with Diabetes Mellitus in Puskesmas II Denpasar Utara. The results of this study were based on Paired Sample Test and Willcoxon showed that there is a significant effect on using the booklet to increase of knowledge, attitudes, and behavior of tooth brushing that each p = 0.00 (p 0.05).